SYSTEMATIC LITERATURE REVIEW: MEWUJUDKAN KEPRIBADIAN OPTIMAL DALAM PERSPEKTIF TEORI HUMANISTIK - Ezzar Arkhan Kautsar Hidayat; M. Ihda Aslami Atqo (Program Studi Bimbingan dan Konseling Pendidikan Islam, 2026)
This article uses the systematic literature review (SLR) method. SLR is a research methodology used to collect, analyze, and synthesize empirical research as well as theoretical reviews on a specific topic. The object analyzed in this article is the optimal personality based on the perspective of humanistic theory. The SLR process is carried out by browsing various relevant sources, including journal databases, books, and other scientific publications. The results of this SLR provide an overview of how humanistic theories, particularly the thinking of Carl Rogers and Abraham Maslow, view optimal personality. This article also provides an in-depth understanding of important aspects in the formation of human personality, such as personal growth, self-actualization, and the development of self-potential, which are the main focus in humanistic theory.